2010
DOI: 10.1186/1471-2458-10-649
|View full text |Cite
|
Sign up to set email alerts
|

Systematic development of a self-regulation weight-management intervention for overweight adults

Abstract: BackgroundThis paper describes the systematic development of an intervention for the prevention of obesity among overweight adults. Its development was guided by the six steps of Intervention Mapping (IM), in which the establishment of program needs, objectives and methods is followed by development of the intervention and an implementation and evaluation plan.MethodsWeight gain prevention can be achieved by making small changes in dietary intake (DI) or physical activity (PA). The intervention objectives, der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…On the other hand, we also think better access to health care can give both health care providers and patients more opportunities to discuss needed lifestyle changes. Either interpretation is consistent with prior studies that reported higher access to care and higher frequency of visits can give providers with opportunities to discuss behavioral change (Berkel, Carlos Poston, Reeves, & Foreyt, 2005;Lerman, 2005;Levy, Finch, Crowell, Talley, & Jeffery, 2007 To improve patients' health conditions, health care providers should acknowledge their patient's excess body weight as a first step in counseling patients on the importance of normalizing energy balance for weight management (van Genugten et al, 2010). Older patients are especially likely to accept risk communication messages and follow recommendations from authorities whom they perceive as credible and trustworthy (Lemyre, Gibson, Zlepnig, Meyer-Macleod, & Boutette, 2009).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…On the other hand, we also think better access to health care can give both health care providers and patients more opportunities to discuss needed lifestyle changes. Either interpretation is consistent with prior studies that reported higher access to care and higher frequency of visits can give providers with opportunities to discuss behavioral change (Berkel, Carlos Poston, Reeves, & Foreyt, 2005;Lerman, 2005;Levy, Finch, Crowell, Talley, & Jeffery, 2007 To improve patients' health conditions, health care providers should acknowledge their patient's excess body weight as a first step in counseling patients on the importance of normalizing energy balance for weight management (van Genugten et al, 2010). Older patients are especially likely to accept risk communication messages and follow recommendations from authorities whom they perceive as credible and trustworthy (Lemyre, Gibson, Zlepnig, Meyer-Macleod, & Boutette, 2009).…”
Section: Discussionsupporting
confidence: 81%
“…This suggests health care providers were more likely to recognize weight problems and discuss healthy eating and physical activity when their patients were moderately or severely obese as compared to being just overweight. This represents a potential missed opportunity for health care providers to guide their patients who are overweight to make changes in dietary intake and physical activity ( van Genugten, van Empelen, Flink, & Oenema, 2010), given that only about 10% of physician-older patient encounters were spent on discussing physical activity, nutrition, or smoking topics (Ory et al, 2007). The 2008 Physical Activity Guidelines for Americans also support that science-based guidance can help Americans aged 65 and older improve their health through appropriate physical activity (U.S. Department of Health Human Services, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Self-reported information on the number of days per week that respondents consumed specific food items was obtained from a FFQ. The FFQ was based on previous questionnaires ( 21 23 ) and asked for the number of days per week that specific food items were consumed (never, < 1 d/week, 1–2 d/week, 3–4 d/week, 5–6 d/week or every day). There were seven food product groups: fruits and vegetables, meat products, bread products, beverages, dairy products, snacks and ready meals.…”
Section: Methodsmentioning
confidence: 99%
“…The personal action plan was sent via email, and adults were offered the possibility to send the action plan to family or friends for social support. The content of the action planning tools was partly based upon the work of Vangenugten et al (2010) and Springvloet et al (2014), who also applied selfregulation techniques into computer-tailored interventions [18,19].…”
Section: Ehealth Interventionmentioning
confidence: 99%